2016
DOI: 10.1371/journal.pone.0167938
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Trichomoniasis in South Korea and Increasing Trend in Incidence, Health Insurance Review and Assessment 2009-2014

Abstract: Trichomoniasis, which is caused by Trichomonas vaginalis, is one of the most common non-viral sexually transmitted infections; however, limited population-based data are available that describe patterns and trends of the disease. We summarized insurance claims of trichomoniasis cases reported during 2009–2014 to South Korea Health Insurance Review and Assessment Service. The average annual incidence in South Korea was 276.8 persons per 100,000 population, and a substantial sex-associated variation was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…The incidence and prevalence of trichomoniasis are known to be varied depending on the population, time, and region, but they are higher in women and older age groups compared to men or younger age groups [ 24 ]. Joo et al [ 25 ] have reported that trichomoniasis emerged as the most common non-viral sexually transmitted diseases (STD) among the total population during 2009–2014. Some overlap occurs, but in the current study, we strived to further analyze more recent data statistically.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and prevalence of trichomoniasis are known to be varied depending on the population, time, and region, but they are higher in women and older age groups compared to men or younger age groups [ 24 ]. Joo et al [ 25 ] have reported that trichomoniasis emerged as the most common non-viral sexually transmitted diseases (STD) among the total population during 2009–2014. Some overlap occurs, but in the current study, we strived to further analyze more recent data statistically.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of T. vaginalis infection varies from region to region, and annual incidence of South Korea is reported to be about 537.2 patients per 100,000 female persons. The age group with highest incidence was 40-49 years [31]. No case was detected in other studies using microscopy [7] and another report stated that vaginitis of T. vaginalis was uncommon in less than 1% of cases [29].…”
Section: Discussionmentioning
confidence: 89%
“…It is understood that misinformation in the context of sexual health entails limitations for people, since they require specific components for access to information ( 11 ) , in addition to expanding the possibilities of contracting an STI. STIs, such as Trichomonas vaginalis, Neisseria gonorrhoeae and Human Papillomavirus, reported by the participants, are considered a global public health problem ( 27 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of these infections was higher in the 20-29 age group ( 1 ) , differing from a study in South Korea where the incidence was higher in women aged 60 years or older. However, the incidence for men increased from 23.7 in 2009 to 15.7 per 100,000 in 2014, with a marked reduction in groups of 40 years or more of this population ( 27 ) . A study carried out in Shanghai reports that, in addition to the incidence of Neisseria gonorrhoeae being the highest of bacterial STIs, it can produce severe complications as well as emerging resistance to third generation cephalosporins, allowing the emergence of a potentially intractable gonorrhea era ( 28 ) .…”
Section: Discussionmentioning
confidence: 99%